Hands-on machine learning with IBM Watson : leverage IBM Watson to implement machine learning techniques and algorithms using Python - Miller, James D. (Software consultant) (Packt Publishing, 2019)
A practical guide on Machine learning with IBM cloud to act as a solid yet concise reference for the readers. You will learn about the role of data representation and feature extraction in machine learning. This book will help you learn how to use the IBM Cloud and Watson Machine learning service to develop real-world machine learning solutions.